Aesthetic improvement: innovating the design and development framework for engineering products - Ibrahim, Mohd Qadafie; Romli, Fairuz Izzuddin; Arep, Hambali (Semarak Ilmu Publishing, 2024)
One of the primary issues with many product design and development processes today is to have a good balance between the elements of form and function. While all products must be able to perform their intended functions, considerations of aesthetic features are also necessary for them to be accepted as a good quality design. However, most available design and development processes of engineering products have been more focused on achieving the functional aspects and tend to treat the aesthetic aspects as less crucial features. This approach has led to many failed functional products in the market as their physical design lacks appealing factors to the targeted customers. To improve the situation, a new product design and development framework is proposed in this study to better facilitate designers or engineers in creating an all-rounded quality product design. This new method is developed based on the findings from a conducted survey among engineering students, who are future product design engineers, to identify and resolve issues with current methods that they use for their design tasks. All in all, the new proposed method is essentially tailored to offer a comprehensive guide for developing beautiful and useful products based on a semantics design approach.